First account of vivipary, including physical and chemical attributes, in fruits of Cereus hildmannianus K. Schum. (Cactaceae) - dos Santos, Everaldo; Luz, Gilberto Codignole; Mangolin, Claudete Aparecida; da Silva Machado, Maria de Fátima Pires; Cota-Sánchez, Jorge Hugo (Revista brasileira de botânica, 2025)
The basic aspects of vivipary, precocious germination within the fruit, are known. Consequently, research on this topic in the Cactaceae has increased in the last two decades and becoming more diversified. The family is amongst the most viviparous-rich angiosperm families together with some mangrove lineages. In this paper we report a new case of facultative vivipary, specifically cryptovivipary, in Cereus hildmannianus K. Schum., a South American columnar species and expand aspects regarding the physico-chemical traits of its fruits. The goals of this investigation were to: 1) report the first occurrence of vivipary in this species and characteristics of viviparous seedlings, and 2) describe some of the physical and chemical attributes of viviparous and nonviviparous fruits, such as size, weight, color, and total soluble solids (°Brix). Our findings show that this is the third account in Cereus Mill., for a 3% vivipary at the generic level. This discovery increases to 78 viviparous species for an overall 5.4% of viviparity family wide. Generally, the number and percentage of vivipary was low, with an average of 22.3 viviparous seedlings from an average of 1319 ungerminated seeds (= 1.7% vivipary/fruit). Statistical analyses indicate that non-viviparous fruits are larger, heavier, have higher content of soluble solids, thicker and brighter pericarp, and more seeds. Agriculturally, these attributes are more appealing to consumers suggesting that normal, non-viviparous fruits, are commercially more desirable; hence, vivipary is a detrimental character in fruit crops.